Digital strategies to promote crowdsourcing open calls for co-creating HIV interventions: a youth community-based participatory approach - Olaoluwaposi Ogunlana; Peter Kalulu; Ucheoma Nwaozuru; Olufunto A. Olusanya; Oluwayemisi T. Olaoluwa; Temitope Ojo; Titilola Gbaja-Biamila; Chiyere Arinze; Lateef Akeem; Lauren Fidelak; Chisom Obi-Jeff; Oliver C. Ezechi; et al. (Frontiers in Digital Health, 2025)
IntroductionThe HIV epidemic disproportionately affects adolescents and young adults (AYA), yet their engagement in HIV programming remains limited. Digital strategies, such as social media campaigns, engage a diverse range of AYA to co-create HIV interventions, but their effectiveness is less known. This study examines the digital strategies employed to engage AYA (ages 14–24) in the participatory design of HIV research and interventions in Nigeria.MethodsWe employed youth participatory action research (PAR), specifically using a crowdsourcing open call strategy to generate innovative ideas from AYA on how community-based organizations can sustain youth-friendly HIV services for at-risk youth. Crowdsourcing involves a group of people solving a problem and then sharing selected solutions with the public. The open call was held between February and March 2024 as part of the Sustaining Innovative Tools to Expand Youth-Friendly HIV Self-Testing (S-ITEST) study. The open call was promoted on social media platforms and through peer youth ambassadors. Submissions were received via various channels, including Google Forms, WhatsApp, and in-person submissions. Social media engagement metrics and open call submission data were collected and analyzed descriptively using R version 4.4.2.Results and discussionUsing social media metrics, the first Instagram post reached 310 people (75% of followers) and generated 43 engagements. The second post reached 272 people (79% of followers) with 29 interactions. The first and second Facebook posts reached 153 and 58 people, respectively, with each post receiving five interactions. We received 123 submissions, with 104 submitted online. Youth in all six geopolitical zones submitted ideas (40 males and 64 females). The mean age of participants was 21.9 (SD =5.35), and most (81%) learned about the open call through digital channels, with WhatsApp (n = 20) being the most common channel. Older youth were more likely to hear about the open call digitally (Mean = 22.5; SD = 5.12) compared to younger participants (Mean = 19.8; SD = 5.87). Building digital communities and opportunities could sustain youth involvement in HIV research. Our findings suggest that digital strategies can complement and optimize in-person engagement to effectively leverage AYA's creativity in co-creating HIV interventions in low-resource settings.